CATATYMNO-IMAGINATIVE PSYCHOTHERAPY IN THE TREATMENT OF PATIENTS WITH ANXIETY-PHOBIC DISORDERS - Guzel, Yusupova (Universitas Islam Negeri Raden Intan Lampung, 2024)
Modern conditions are not sufficient for a psychotherapist to study and apply only one modality in practice. Requires a level of professional competence that allows to use the psychotherapeutic potential of various psychotherapeutic modalities, in combining them in their work. In this case, the multimodal (integrative) approach of using the method of catatymno-imaginative symbolic drama allows fully implementing the principle of an individual approach to each patient, providing the opportunity to take into account not only the nature of his mental disorders, but also personal characteristics such as the level of intelligence, emotional state, and also behavior. This research aims to reveal the peculiarities of organizing and implementing psychotherapy using the catatym-imaginative drama symbol method involving 14 outpatients in various departments of the State Budget Agency who have been diagnosed with anxiety based on ICD-10. The testing method used in this research was the Sheehan Anxiety Scale and anxiety assessment techniques based on the Spielberger-Khanin theory. The measurements were carried out at the initial session of the meeting and the final session (8th meeting). The method used is combined with body-oriented psychotherapy. The results of this study showed that respondents with anxiety-phobic disorders had a positive correlation, and this relationship was more pronounced before training. Pearson correlation coefficient (r) was 0.87 (before training) and 0.79 (after training). It can be concluded that in the treatment of patients with anxiety-phobic disorders, the method of catatim-imaginative therapy significantly reduces the negative symptoms.